James Chesnut papers - Chesnut, James, 1815-1885.
Correspondence during Chesnut's service as chief of militia on the South Carolina Executive Council, Columbia, S.C. Relates primarily to recruitment, military finances, and conditions throughout South Carolina. Correspondents include Jefferson Davis, Robert E. Lee, and local government and Confederate army officials.
U.S. senator from South Carolina (1858-1861), lawyer, and plantation owner.
Collection material in English.
Keywords: Davis, Jefferson, -- 1808-1889 -- Correspondence; Lee, Robert E. -- 1807-1870 -- Correspondence; Confederate States of America. -- Army -- Finance; Confederate States of America. -- Army -- Recruiting, enlistment, etc; Columbia (S.C.) -- History; South Carolina -- History -- Civil War, 1861-1865.; Lawyers; Plantation owners; Senators, U.S. Congress